EAU guidelines on urethral trauma - Martínez-Piñeiro, Luis; Djakovic, Nenad; Plas, Eugen; Mor, Yoram; Santucci, Richard A.; Serafetinidis, Efraim; Turkeri, Levent N.; Hohenfellner, Markus (European urology, 2010)
These guidelines were prepared on behalf of the European Association of Urology (EAU) to assist urologists in the management of traumatic urethral injuries. To determine the optimal evaluation and management of urethral injuries by review of the world’s literature on the subject.
Gesehen am 23.05.2023